Doppler Ultrasonography in Subfertile Male - Sharif, Md Mofazzal; Sudipta, Omarandra Saha; Rahman, Md Towhidur; Khatun, Mst Monira; Rekha, Khaleda Parvin (KYAMC Journal, 2020)
Imaging modality, especially Doppler Ultrasonography is a widely used and well tolerated modality for evaluation of pathologic conditions of the testes. Recent technical advances of US applications and post processing developments have enabled new aspects in the structural and functional analysis of testicular tissue and therefore male fertility. This review covers the most relevant approaches regarding Doppler ultrasonography of testis due to recent technical advances. KYAMC Journal Vol. 11, No.-2, July 2020, Page 100-103